Measurement of forward top pair production in the dilepton channel in pp collisions at √s = 13 TeV - Aaij, Roel; D'Argent, Philippe; Bachmann, Sebastian; Berninghoff, Daniel; Braun, Svende; Comerma-Montells, Albert; De Cian, Michel; Dziewiecki, Michal; Esen, Sevda; Gerick, David; Grünberg, Oliver; Han, Xiaoxue; et al. (Journal of high energy physics, 2018)
Forward top quark pair production is studied in pp collisions in the μeb final state using a data sample corresponding to an integrated luminosity of 1.93 fb−1 collected with the LHCb experiment at a centre-of-mass energy of 13 TeV. The cross-section is measured in a fiducial region where both leptons have a transverse momentum greater than 20 GeV and a pseudorapidity between 2.0 and 4.5. The quadrature sum of the azimuthal separation and the difference in pseudorapidities, denoted ΔR, between the two leptons must be larger than 0.1. The b-jet axis is required to be separated from both leptons by a ΔR of 0.5, and to have a transverse momentum in excess of 20 GeV and a pseudorapidity between 2.2 and 4.2. The cross-section is measured to beσtt¯=126±19stat±16syst±5lumifb$$ σ_{t\overline{t}}=126± 19\left(stat\right)± 16\left(syst\right)± 5\left(lumi\right)fb $$where the first uncertainty is statistical, the second is systematic, and the third is due to the luminosity determination. The measurement is compatible with the Standard Model prediction.